Can avoid kitchen garbage classification processing system of homology pollution - XU HAORAN (2017)
The utility model discloses a can avoid kitchen garbage classification processing system of homology pollution, this system includes: protide processing system and carbohydrate class processing system, wherein, the protide processing system include: cook unit and the comminution unit that link to each other, the carbohydrate class processing system include: squeeze the unit. Kitchen garbage classification processing system still includes: dry unit to comminution unit, squeeze the unit and all link to each other with dry unit. The application method of this system is still disclosed simultaneously. The utility model discloses the sick fodder of homology can be effectively avoided having and the poultry domestic animal is polluted to the feed quality who obtains is higher. 本实用新型公开了种能够避免同源污染的餐厨垃圾分类处理系统，该系统包括：蛋白类处理系统和碳水化合物类处理系统，其中，蛋白类处理系统包括：相连的蒸煮单元和粉碎单元，碳水化合物类处理系统包括：压榨单元。餐厨垃圾分类处理系统还包括：干燥单元，并且粉碎单元、压榨单元均与干燥单元相连。同时还公开了该系统的使用方法。本实用新型能够有效避免带有同源病饲料污染家禽家畜，并且得到的饲料品质较高。